Plant Stress Physiology Perspectives in Agriculture - Hasanuzzaman, Mirza; Nahar, Kamran (Physiology, 2022)
This book includes ten chapters addressing various aspects of plant stress physiology, including plant responses and tolerance to abiotic and biotic stress. These chapters summarize recent findings on the physiological and molecular mechanisms of stress tolerance. They also discuss approaches to enhancing plant productivity via stress tolerance mechanisms. This book is useful for undergraduate and graduate students, teachers, and researchers in the field of plant physiology and crop science.